Perancangan Sistem Informasi Pengelolaan Dana Masjid Berbasis Web Menggunakan Unified Modeling Language (UML) - Manja Purnasari; Yessi Hartiwi; Nurhayati Nurhayati (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Information needs among the people at the moment is very large, including information on the management of fund mosque around them. The administrative system related to the processing of financial data is an important thing for an agency, be it government institutions, community institutions, or religious institutions such as mosques. Mosques are religious institutions that are managed independently by the community. As one of the institutions that manage funds collected voluntarily from the community, accountability and transparency are needed in its management. Masjid Al-Istiqomah Muaro Jambi in fund management still uses manual methods, namely by recording on the cash book so as to allow inaccuracy of data in recording incoming and outgoing funds and difficulties in finding previous data, as well as the absence of transparency of the overall funds owned by The Al-Istiqomah Mosque to the local community. This study aims to make it easier for mosque administrators to manage mosque funds and provide financial information quickly, precisely and accurately to the public. The model used in this study is unified modelling language (UML) and prototype design using figma application. This research resulted in a prototype of a web-based information system for managing funds mosque and their reporting.